2015
DOI: 10.1097/pcc.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Electrographic Seizures by Critical Care Providers Using Color Density Spectral Array After Cardiac Arrest Is Feasible*

Abstract: Objective To determine the accuracy and reliability of electroencephalographic seizure detection by critical care providers using color density spectral array (CDSA) electroencephalography (EEG). Participants Critical care providers (attending physicians, fellow trainees and nurses.) Interventions A standardized powerpoint CDSA tutorial followed by classification of 200 CDSA images as displaying seizures or not displaying seizures. Measurements and Main Results Using conventional EEG recordings obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…Multiple two hour tracings could be made from the same patient. A pediatric electroencephalographer categorized these images as having no seizures, seizures or status epilepticus (15). Seizures were defined as abnormal paroxysmal events lasting more than 10 seconds or shorter if associated with a clinical change, with a temporal-spatial evolution in morphology, amplitude and frequency.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Multiple two hour tracings could be made from the same patient. A pediatric electroencephalographer categorized these images as having no seizures, seizures or status epilepticus (15). Seizures were defined as abnormal paroxysmal events lasting more than 10 seconds or shorter if associated with a clinical change, with a temporal-spatial evolution in morphology, amplitude and frequency.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for cEEG tracings acquisition and conversion to aEEG and CDSA tracings are described in our group’s previous published work (15). The CDSA tracings and corresponding aEEG tracings were the same as those used in our previous study (15).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue Topjian and colleagues (5) investigated the sensitivity and reliability of color density spectral array (CDSA), a quantitative EEG modality, in detecting electrographic seizures by the pediatric critical care providers. They demonstrated that the pediatric critical care providers with varying experience level could retrospectively identify electrographic seizures based on cEEG-derived CDSA images with reasonable accuracy and reliability following brief training.…”
mentioning
confidence: 99%